2023
DOI: 10.3390/pathogens12020209
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps and Their Possible Implications in Ocular Herpes Infection

Abstract: Neutrophil extracellular traps (NETs) are net-like structures released from neutrophils. NETs predominantly contain cell-free deoxyribonucleic acid (DNA) decorated with histones and neutrophil granule proteins. Numerous extrinsic and intrinsic stimuli can induce the formation of NETs such as pathogens, cytokines, immune complexes, microcrystals, antibodies, and other physiological stimuli. The mechanism of NETosis induction can either be ROS-dependent or independent based on the catalase producing activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…The latter has been previously implicated in bacterial sepsis, fungal infections, autoimmune disorders, and cancer but not in HSV-1 infection. 11 We also made a striking observation that HSV-1 induced rapid NETosis occurs within the first hour of infection, which is much faster than the conventional NETosis induced by PMA, which takes about 4 hours. 25 This suggests that HSV-1 triggers a distinct mechanism of NETosis that involves a rapid release of chromatin without extensive decondensation or degradation.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The latter has been previously implicated in bacterial sepsis, fungal infections, autoimmune disorders, and cancer but not in HSV-1 infection. 11 We also made a striking observation that HSV-1 induced rapid NETosis occurs within the first hour of infection, which is much faster than the conventional NETosis induced by PMA, which takes about 4 hours. 25 This suggests that HSV-1 triggers a distinct mechanism of NETosis that involves a rapid release of chromatin without extensive decondensation or degradation.…”
Section: Discussionmentioning
confidence: 70%
“…On one hand, NETs could act as a physical barrier to prevent viral spread and as a source of antimicrobial peptides to kill or inhibit viral replication. 11 On the other hand, NETs could also cause collateral damage to the host tissue by inducing inflammation, oxidative stress, and apoptosis. To address this question, we depleted neutrophils from the cornea using Ly6G antibodies before infecting mice with HSV-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is presumed that there might be neutrophil infiltration to the site of the infection, which releases neutrophil extracellular traps (NETs) as a primary defense mechanism against the infection. 37 Studies have shown the NETs play a role in fungal and bacterial ocular infections, as well as in viral infections such as influenza virus and SARS–CoV-2. 38 41 However, their role in ocular HSV-1 infections remains a mystery.…”
Section: Discussionmentioning
confidence: 99%
“…In the human immune system, NETosis is a double-edged sword. On the one hand, NETosis has been described as a neutrophil defense mechanism of the organism that traps and destroys a wide range of pathogens involved in anti-inflammatory, antibacterial and antiviral immune responses, including Gram-positive bacteria ( von Kockritz-Blickwede and Winstel, 2022 ), Gram-negative bacteria and their virulence factors ( Sung et al, 2022 ), fungi ( Huang et al, 2022 ), protozoa ( Conejeros et al, 2022 ) and viruses ( Kapoor and Shukla, 2023 ). NETosis is also involved in the normal regeneration and repair of blood vessels.…”
Section: Mechanisms Of Netosismentioning
confidence: 99%